2023
DOI: 10.3390/coatings13010087
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Rubber Aggregate-Combined Permeable Concrete Mixture in Sponge City Construction

Abstract: Permeable concrete is a new type of pavement material, which can effectively improve the urban flood discharge system, and is of great significance to the construction of sponge city. In order to optimize the use effect of permeable concrete and improve the application value of permeable concrete in permeable road engineering, the combination of rubber aggregate and permeable concrete is proposed, and the mix ratio of rubber permeable concrete mixture material is designed, which is applied to the engineering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…In Equation ( 2), K 30 represents the infiltration efficiency of rainfall for 30 min, m 30 represents the water output (g) at this moment, and ρ w represents the density of water, which is taken as 1 g/cm 3 . The test definition of water retention is the material particles between the voids existing and surface water absorption pores in the rainfall stagnation of rainwater, using volume water retention rate to characterize [23][24][25][26][27][28][29]. Volumetric water retention is the ratio of the volume of the structural layer of the material to the amount of water retained, while the amount of water retained is the difference between the total amount of water that comes out and the total amount of rainfall at each moment.…”
Section: Test Methods and Proceduresmentioning
confidence: 99%
“…In Equation ( 2), K 30 represents the infiltration efficiency of rainfall for 30 min, m 30 represents the water output (g) at this moment, and ρ w represents the density of water, which is taken as 1 g/cm 3 . The test definition of water retention is the material particles between the voids existing and surface water absorption pores in the rainfall stagnation of rainwater, using volume water retention rate to characterize [23][24][25][26][27][28][29]. Volumetric water retention is the ratio of the volume of the structural layer of the material to the amount of water retained, while the amount of water retained is the difference between the total amount of water that comes out and the total amount of rainfall at each moment.…”
Section: Test Methods and Proceduresmentioning
confidence: 99%
“…In recent years, the rapid advancement of urbanization has led to a sharp increase in building density and land surface coverage, triggering a transformation in the urban surface water circulation system and frequent occurrence of internal flooding [1]. Porous concrete, known for its excellent permeability and drainage capacity [2][3][4][5], is typically composed of cement mortar and aggregates and widely applied in areas such as parking lots, permeable road surfaces, and riverbank slopes [6][7][8][9][10]. With its unique porous structure, porous concrete plays a crucial role in mitigating urban flood risks and alleviating the urban heat island effect [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have been interested in producing and developing ultra‐high‐performance concrete (UHPC) properties and their applications, 1–3 in addition to studying the possibility of using nanomaterials (NMs) of industrial waste to improve concrete properties and reduce production costs 4–8 . The main distinguishing features are the superior UHPC's mechanical strength, which is not less than 150 MPa; the tensile strength, which is greater than 8 MPa at 28 days test age of; and its ultra‐durability 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 For these reasons, the researchers set out to study the possibility of reducing the cement content through partial replacement of cement with supplemental cement materials (SCMs). 19,22,23 Previous studies have indicated the possibility of using SCMs from industrial by-products, such as silica fume, 24,25 fly ash (FA), 26,27 pulverized ground granulated blast furnace slag, 3,28 ferrosilicon powder 29 and metakaolin. 30 Accordingly, many studies have used FA as SCMs to decrease the cement content consumed in UHPC and improve its properties.…”
mentioning
confidence: 99%